Cone-beam computed tomography: Hype and facts - Vivek Velayudhan Nair; Bindu J Nair (Wolters Kluwer Medknow Publications, 2014)
Cone beam computed tomography (CBCT) is a relatively new gadget in the field of clinical CT technology. CBCT has been projected as a low-dose alternative to medical CT, with a wide range of applications, and it is said to have paved the way for a paradigm shift in the role of imaging in dentistry from diagnosis to image guidance. However, several questions remain regarding the applicability of CBCT in dentistry, as some of the applications suggested appear to be applications for the sake of an application. This article attempts to look into the hype and facts of cone beam CT.